Understanding people's willingness to implement measures to manage human-bear conflict in Florida - Telesco, David, speaker; Pienaar, Elizabeth F., speaker; Barrett, Sarah, speaker; Breck, Stewart, moderator; International Wildlife Ranching Symposium, producer (Colorado State University. Libraries, 2014)
In 2009 the Florida Fish and Wildlife Conservation Commission (FWC) began surveying individuals who reported human-bear conflicts. The purpose of this survey is to assess whether individuals take actions recommended by the FWC to reduce or eliminate conflicts. Using this data set, we determined which factors influence the likelihood that surveyed individuals will follow the advice provided by the FWC for managing human-bear conflicts. We find outreach efforts by the FWC increase the probability that people who report conflicts to the agency adopt recommended measures to reduce these conflicts. Our results suggest that outreach efforts by wildlife agencies increase the likelihood that people will alter their behavior to reduce human-bear conflicts.
Moderator: Stewart Breck.
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
Video presenter: Elizabeth Pienaar.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Wildlife management -- Congresses; Range management -- Congresses